Hand Planter for the Developing World: Factor Testing and Refinement. Issue 1 (6th September 2018) - Dhillon, Jagmandeep S.; Omara, P.; Nambi, E.; Eickhoff, E.; Oyebiyi, F.; Wehmeyer, G.; Fornah, A.; Ascencio, E. N.; Figueiredo, B. M.; Lemings, R.; Lynch, T.; Ringer, J.; et al.
Abstract : Core Ideas: Developing world maize producers desperately need better planting methods. OSU hand planter delivers safety, convenience, and increased maize yields for producers managing highly marginal landscapes. Same area of maize planted in the USA (30 million ha) is planted in the developing world on highly marginal slopes. Maize ( Zea mays L.) production in the developing world takes place on marginal landscapes using indigenous planting methods that conflict with modern hybrids, and the chemically treated seeds being used. In 1987, a mechanical planter was imagined that could replace indigenous planting methods used in many developing countries where maize is produced on marginal landscapes. Over two decades, controlled variables were evaluated with the aim of delivering an improved planter capable of singulating maize seed with each planter strike, and that would ensure uniform plant stands. This hand planter, presently termed GreenSeeder was further designed to deliver mid‐season fertilizer N via the use of an alternative internal drum. To secure singulation for each planter strike, many seed sizes, planter weights, brush strengths, drum cavity sizes, and operators were evaluated. Results showed that when seed size was large (<3000 seeds kg −1 ) and the 260‐20 internal drum was employed, the ability to singulate with no misses was high. When the 450S internal drum was used, seed sizes that were smaller (>3500 seeds kg −1 ) had higher singulation and lower misses. An efficiency index encumbering these parameters was developed that was highly correlated with final grain yield. In‐country design and manufacturing should account for ranges in seed size that work with the present design, drum cavity depth, and angle. Because this planter can easily accommodate mid‐season fertilizer N application, adoption of this device should deliver increased grain yields and fertilizer N use efficiency.